Racism Issues and the Impact of Racism Depicted on United Kingdom Movies - dini aprilia; bahren bahren; chandri febri santi (English Language, Linguistics, Literature, And Education Journal, 2022)
Racism is always an interesting topic to debate and from the movie A United Kingdom by Amma Asante. The researcher wants to feeling the racism issues and impact of racism, and to feeling the racism that faced in the main character of Seretse Khama. The researcher used qualitative descriptive method. It is suitable for this research because when people analyze it, there are many interpretations and perceptions, and the qualitative method can bind the whole differences of interpretation and perception. The researcher took the data from the dialogues that contains racism which was taken from the script and movie. There are three issues of racism. First, discrimination the act of racism is the negative treatment from white people to black people. Second, prejudice was given by white people to people of their color for no reasons. The third, segregation was given by white people to black people by a great separation between whites and blacks. three impact of racism that experienced by main character Seretse Khama. Those are: Grief, rage, and humiliation.